Skin Matters: Identifying Pain Mechanisms and Predicting Treatment Outcomes - Edward A. Shipton (Neurology Research International)
The skin acts as a complex sensory organ. The emerging new data on peripheral pain mechanisms from within the skin is presented. This data has led to new insights into the potential pain mechanisms for various pain conditions including neuropathic pain (from small fiber neuropathies) and Complex Regional Pain Syndrome. The somatosensory neurons that innervate our skin constantly update our brains on the objects and environmental factors that surround us. Cutaneous sensory neurons expressing nociceptive receptors such as transient receptor potential vanilloid 1 channels and voltage-gated sodium channels are critical for pain transmission. Epidermal cells (such as keratinocytes, Langerhans cells, and Merkel cells) express sensor proteins and neuropeptides; these regulate the neuroimmunocutaneous system and participate in nociception and neurogenic inflammation. In the past two decades, there has been widespread use of modalities such as punch skin biopsies, quantitative sensory testing, and laser-evoked potentials to evaluate small caliber nerve fibers. This paper explores these laboratory techniques as well as the phenomenon of small fiber neuropathy. Treatment using transdermal drug delivery is discussed. There is potential for these findings to predict treatment outcomes in clinical practice and to develop new therapies for different pain conditions. These findings should enhance the physician's ability to evaluate and treat diverse types of pain.